2008
DOI: 10.1158/1055-9965.epi-08-0761
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Urine Profile of 4-(Methylnitrosamino)-1-(3-Pyridyl)-1-Butanone Metabolites and N7-Methylguanine in Urothelial Carcinoma Patients

Abstract: A major carcinogen, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), is present in cigarette smoke and its metabolite, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), is used as an exposure biomarker for environmental tobacco smoke (ETS). This metabolite (NNAL) can be either detoxified into glucuronidated NNAL (NNAL-Gluc) or activated into an unstable reactive metabolite that methylates DNA along with formation of 4-hydroxy-4-(3-pyridyl)-butyric acid [hydroxy acid (HA)]. Therefore, the carcinogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…NNK is the potent carcinogen in cigarette smoke and TCDD is the most potent AhR agonist among dioxins. Because NNK metabolites and TCDD are detectable in human specimens of the general population [26][27][28][29], it is possible that NNK may interact with TCDD and enhance cancer risks in the general population, such as lung cancer. In our present study, we demonstrated that the combined treatment of NNK and TCDD at non-carcinogenic doses significantly increased the incidence of lung adenoma in A/J mice.…”
Section: Discussionmentioning
confidence: 99%
“…NNK is the potent carcinogen in cigarette smoke and TCDD is the most potent AhR agonist among dioxins. Because NNK metabolites and TCDD are detectable in human specimens of the general population [26][27][28][29], it is possible that NNK may interact with TCDD and enhance cancer risks in the general population, such as lung cancer. In our present study, we demonstrated that the combined treatment of NNK and TCDD at non-carcinogenic doses significantly increased the incidence of lung adenoma in A/J mice.…”
Section: Discussionmentioning
confidence: 99%
“…5 Linearity was observed for NNAL and hydroxy acid compounds (r 2 ϭ 0.999), with detection limits ranging from 0.2 to 2.4 pg on column and 0.01 to 0.12 ng/ml in injected samples. Precision and accuracy were determined by analyzing urine collected from a nonsmoker spiked with 1 ng/ml d 3 -NNAL (quality control samples).…”
Section: Analysis Of Nnk Metabolitesmentioning
confidence: 92%
“…4 Environmental tobacco smoke is thought to be a risk factor for bladder cancer. 5 The nicotine derived, tobacco specific nitrosamine NNK has also been linked to tobacco related human malignancies. 6 NNK is a procarcinogen that requires metabolic activation by cytochrome P450 enzymes to exhibit its carcinogenic effects.…”
Section: Abbreviations and Acronymsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be formed by the α-hydroxylation pathway of NNK, but is not specific to NNK since adduct can also be formed by other methylating agents. A moderate correlation was reported between free NNAL and N 7 -MEG in a group of urothelial carcinoma patients split between smokers and non-smokers (Lee et al, 2008). BPDE-haemoglobin adducts but not the albumin adduct were highly correlated with the urinary polyaromatic hydrocarbon 1-hydroxypyrene (Tzekova et al, 2004).…”
Section: Introductionmentioning
confidence: 98%